Estimating dispersal of coral larvae for ecosystem management in Tioman island - Hanapiah, Muhammad Faiz; Ahmad, Zuhairi; Saad, Shahbudin (2016)
Dispersal of coral larvae and successive recruitment are important for ecosystem man-agement especially in marine protected areas to estimate how far larvae travel in the water and settle on substrates. Information on dispersal distance is crucial to determine the magnitude of self-recruitment and inter reefs connectivity. In this study, dispersal of larvae particles was investigated by applying Langragian particle tracking module integrated with 2-dimensional, hydrodynamic, flexible mesh model (MIKE 21 FM). Simulation were carried out for two distinct pelagic larvae durations (PLD); optimal PLD and extensive PLD during major spawning activities in April 2014 at four source reefs namely Genting Village, Renggis Island, Teduh Bay and Juara Bay. Results indi-cated that most of coral larvae particles from each source reef dispersed closer to natal reef during optimal PLD (5-7 days after spawning) suggesting self-recruitment from local larvae pool play major role in shaping coral reef assemblages. Extended PLD (14 days after spawning) may increase connectivity between reefs as coral larvae travel far-ther. However, successful recruitment rates may decrease due to larval mortality and predation. Therefore strategic ecosystem management and habitat restoration in Ti-oman Island is needed since reef resilience may depends on local larvae pool.